Laser-synthesised magnesium nanoparticles for amino acid and enzyme immobilisation - Anesu Nyabadza; Chunxu Shan; Ronan Murphy; Mercedes Vazquez; Dermot Brabazon (Elsevier, 2023)
Enzyme and amino acid immobilisation increase the efficiency of biochemical reactions while facilitating a mechanism for their delivery to tissues. Herein, clean MgNPs were fabricated via laser ablation and were mixed and ultrasonicated together with trypsin and glutamine for immobilisation. The as-synthesised MgNPs of various concentrations exhibited human dermal fibroblast cell growth-promoting effects and an improved dynamic reciprocity environment as demonstrated via cell adhesion. Adsorption was the mechanism used for immobilising amino acids and enzymes onto MgNPs. The resulting composites, visualised via FESEM, appeared as highly connected needle structures. Immersion in DI water was employed for chemical elution while centrifugation at 12,000 rpm and filtration through 200 nm pore sizes were applied to induce physical elution. The microstructure of the MgNPs-trypsin composites did not change significantly after elution while the MgNPs-trypsin composites showed morphological changes from a monolithic structure to a disaggregated structure.